No scalpel vasectomy: a cross-sectional study of knowledge, attitude and practice of gynaecologists - Godbole, Girish P.; Oka, Gauri A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In spite of no scalpel vasectomy (NSV) being cheaper and safer, female sterilisations account for the majority of sterilisations performed worldwide. Research has focussed more on the “demand” and less on the “provider” side. Gynaecologists can be front-runners for the cause of population control in India. Hence, authors decided to estimate the knowledge of gynaecologists, their attitude and prevalent practice of NSV. Methods: Cross-sectional study. Interviewer-administered questionnaire used for face-to-face data collection from gynecologists registered with the Pune Obstetric and Gynecological Society. Results: Out of 447 gynecologists, 158 (35.3%) were males and 289 (64.7%) females. Mean age was 46.3 years ± 12.1 years, (range 24-80 years). Only 14 (3.1%) were trained in performing NSV. Only a minority knew about type of anaesthesia used (1.8%) and number of accesses needed (48.1%) for NSV. Only 40.7% and 18.1% knew about time to resume sexual activity and number of ejaculations to be covered by additional contraceptives after NSV respectively. More than half [258 (57.7%)] were willing to undergo training in NSV. Among those unwilling for training, female and older gynecologists (≥40 years) significantly outnumbered male and younger gynecologists (76.5% Vs. 23.5%; p=0.000 and 78.8% Vs. 21.2% respectively; p=0.000). Majority (79.9%) referred a couple willing for NSV to surgeons or urologists or advised female sterilization (17%). Conclusions: Knowledge of gynecologists about NSV was inadequate. Minority were trained in performing NSV. Male and younger gynecologists were willing to undergo training in NSV. Most preferred practices were referring couples elsewhere or advising female sterilization.